Protection mechanisms of blast furnace hearth linings achieved through titanium additions to the burden - Justus, S. M. (2003)
The protection mechanisms of refractory linings both at the slag and pig-iron levels associated with conventional techniques of titanium addition to the blast furnace burden were investigated. The results were derived from a post mortem study on CSN's Blast Furnaces 2 and 3, as well as laboratory simulations carried out using two different refractory carbon materials. Based on the understanding of these mechanisms, it is possible to improve the efficiency of conventional techniques for titanium addition to the blast furnace burden.